Heterocyclic tri-urea isocyanurate bridged groups modified periodic mesoporous organosilica synthesized for Fe(III) adsorption - Rana, Vijay Kumar; Selvaraj, M.; Parambadath, Surendran; Chu, Sang-Wook; Park, Sung Soo; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Journal of Solid State Chemistry, 2012)
To achieve a high level of heavy metal adsorption, 1,1',1 `'-(1,3,5-triazine-2,4,6-triyl)tris(3-(3-(triethoxysilyl) propyl)urea) (TTPU) was synthesized as a novel melamine precursor and incorporated on the silica surface of periodic mesoporous organosilica (PMO). The melamine modified PMOs (MPMOs) were synthesized under acidic conditions using TTPU, tetraethylorthosilicate (TEOS) and Pluronic P123 as a template and the modified PMOs were characterized using the relevant instrumental techniques. The characteristic materials were used as adsorbents for the adsorption of Fe(III) ions. Fe(III) adsorption studies revealed MPMO-7.5 to be a good absorbent with higher adsorption efficiency than other MPMOs. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Adsorption efficiency; Fe(III) adsorption; Melamine; Periodic mesoporous organosilica (PMO)